The Linguistic Foundation of Transformational Generative Grammar (T.G.G.): Noam Chomsky: The role of Noam Chomsky in the development of Transformational Generative Grammar theory (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Transformational Generative Grammar (TGG) is a branch of generative grammar theory in linguistics that focuses on natural languages. Transformational Grammar is another name for Transformational Generative Grammar, which is a language analysis method. It depicts the link between the many aspects of a sentence and the potential sentences in the English language, as well as the method or procedures that are referred to as sentence transformations to convey semantics using ‘surface structures' and 'deep structure.' In this paper introduction of Noam Chomsky and brief introduction of Transformational Generative Grammar (T.G.G.)